2013
DOI: 10.1039/c3an00659j
|View full text |Cite
|
Sign up to set email alerts
|

An in-source stretched membrane inlet for on-line analysis of VOCs in water with single photon ionization TOFMS

Abstract: An in-source, stretched, hollow fiber membrane (HFM) inlet has been developed to improve the sensitivity of on-line time-of-flight mass spectrometry (TOFMS) with a vacuum ultraviolet (VUV) lamp based single photon ionization (SPI) source for the direct analysis of liquid samples. A 2-cm HFM was stretched to 8 cm in length, and placed in the ion source and directly under the VUV lamp window with a distance of 15 mm. Compared with the conventional flow-through configuration under the same experimental conditions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…The analytes with ionization energies (IEs) lower than 10.6eV can be ionized by SPI. The IEs for most VOCs are below 10.6 eV; 25 thus, SPI is suitable for the ionization of VOCs with a certain selectivity [26][27][28] Compared with electron impact ionization, SPI is a soft ionization method with less fragmentation. 29 In our study, clean spectra with little background noise were observed because the photon energy in the SPI source is not sufficient to ionize the gases (i.e., H 2 O, N 2 , O 2 , and CO 2 ) from the matrix/background.…”
Section: Spi Sourcementioning
confidence: 99%
“…The analytes with ionization energies (IEs) lower than 10.6eV can be ionized by SPI. The IEs for most VOCs are below 10.6 eV; 25 thus, SPI is suitable for the ionization of VOCs with a certain selectivity [26][27][28] Compared with electron impact ionization, SPI is a soft ionization method with less fragmentation. 29 In our study, clean spectra with little background noise were observed because the photon energy in the SPI source is not sufficient to ionize the gases (i.e., H 2 O, N 2 , O 2 , and CO 2 ) from the matrix/background.…”
Section: Spi Sourcementioning
confidence: 99%
“…SPI was applied for the analysis of complex samples such as volatile organic compounds (VOCs). 32,111,112 SPI was accomplished using a commercial krypton discharge lamp (10.6 eV) with a photon ux of about 10 11 photons per s, while the CI was achieved through ion-molecule reactions with O 2 + reactant ions generated by photoelectron ionization.…”
Section: Vuv Lamp-based Charge-transfer Ionization (Vuv Lamp-based Cti)mentioning
confidence: 99%
“…PI is another widely used soft ionization method for online mass spectrometry. It is suitable for pressure from vacuum to atmospheric pressure. Light sources, such as synchrotron radiation-based, laser-based, and low pressure discharge VUV lights, were mostly utilized.…”
mentioning
confidence: 99%